The Rotifer fauna of Guatemala and Belize: survey and biogeographical affinities - Alma Estrella García-Morales; Manuel Elías Gutiérrez (Revista de Biología Tropical, 2007)
Rotifer samples were obtained from 29 localities in northern Guatemala and central-southern Belize during March 2000 and June 2001. A total of 119 species were identified. Ten selected taxa are illustrated and commented: Euchlanis semicarinata, Lepadella apsicora, L. cryphaea, Lecane curvicornis f. lofuana, L. whitfordi, Monommata maculata, Scaridium bostjani, Trichocerca elongata f. braziliensis, and T. hollaerti. The species Lepadella rhomboidula is a first record for the American Continent. The species are 71 % cosmopolitan, 6 % tropicopolitan, and 4.2 % restricted to the subtropics. The Guatemala species number range was Petén-itza lake (53 taxa), and Raxruja pool (three). La Democracia pool (49 taxa), and the Blue Hole sink-hole (six species) were the extremes in Belize. in total, 68 of the recorded taxa are new for Guatemala and 91 for Belize. Additionally, 47 species are registered by the first time in Central America. A comparison between these two countries and Mexico revealed that the south part of the latter conform a cluster with them, emphasizing the transitional character of this region between the Nearctics and the Neotropics. Furthermore, Guatemala and Belize have differences in species assemblages, as a response to the nature of their particular environments and topographical accidents. Rev. Biol. Trop. 55 (2): 569-584. Epub 2007 June, 29. El análisis de muestras procedentes del norte de Guatemala y centro-sur de Belice, recolectadas en marzo de 2000 y junio de 2001, dio como resultado la presencia de 119 especies. Se presenta una breve descripción de diez taxones seleccionados con base en sus distribuciones restringidas en ciertos ámbitos de América y el viejo continente: Euchlanis semicarinata, Lepadella apsicora, L. cryphaea, Lecane curvicornis f. lofuana, L. whitfordi, Monommata maculata, Scaridium bostjani, Trichocerca elongata f. braziliensis,y T. hollaerti. Por primera vez se informa Lepadella rhomboidula en el continente americano. Las especies registradas incluyen 71 % con distribución cosmopolita y 6 % tropicopolitas; 4.2 % se encuentran restringidas a los subtrópicos. La máxima y mínima diversidad de especies en Guatemala correspondió al lago Petén-itza (con 53 taxones) y al estanque Raxruja (con tres). El estanque La Democracia (con 49 taxones) y el Blue Hole (con seis) fueron máximo y mínimo en Belice. Del total encontrado, 47 especies se registran por primera vez en Centroamérica. Una comparación entre la fauna de rotíferos de estos dos países y México refleja una similitud; sin embargo, también se aprecian ciertas diferencias que permiten establecer un gradiente que va de la región neotropical hacia la neártica.